Executive Committee Minutes 2017-02-23 - Academic Senate:::::::::
Agenda – Approved. Minutes of 2/9/17 – Approved. Chair Report. President Report. SSU Academic Foundation name change consultation. Revision to the Student Grievance policy - referred back to SAC. Revision to the Multiple Subjects Teacher Credential approved for the Senate consent calendar. Resolution on the Investiture of President Sakaki approved for the Senate agenda. Provost Report. Questions for the Vice President of Administration and Finance. Revision of Faculty Consultation in University Decision Making policy & rescinding Faculty Consultation in Budgetary Matters policy – referred back to APARC. Vice Chair Report. Vice President of Student Affairs Report. EPC Report. Questions for FSAC. Office Hour policy discussion resulted in Faculty Office Hours and Availability policy – approved for Senate agenda. Senate agenda approved. CFA Report. SEC Report.